Reference Criteria For Forehand Shot In Badminton According To Performance Time And Accuracy Of Middle and South Club Players U17 - Shihab, Zehra; Jalab, Mohammed (Journal of Physical Education, 2015)
The importance of the research lies in designing reference criteria for forehandshot in badminton according to performance time and accuracy. The problem of the researchwas that all tests designed by previous researchers concentrate on accuracy only, theresearchers proposed the necessity of building a test according to accuracy and time ofperformance so as to combine skill performance tests with skill performance duringcompetition.The researchers used the descriptive method. The results showed that the testsprepared by the researchers can be used to test middle and south governorate Badmintonplayers under 17. Finally the researchers recommended using these tests during badmintonplayers' selection by the national badminton federation.